2016
DOI: 10.1039/c6ay00513f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of difenoconazole pesticides in pak choi by surface-enhanced Raman scattering spectroscopy coupled with gold nanoparticles

Abstract: Difenoconazole is a highly effective and broad-spectrum triazole bactericide pesticide and was generally applied to protect and cure foods such as vegetables and fruits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In 2016 Huang and coauthors reported the use of colloidal gold nanoparticles purchased from OptoTrace Technologies to detect lowconcentration DFC in pak choi extract. 13 In that study the authors achieved a DFC detection limit of 0.413 mg L À1 . In a more recent publication (2019) Wang et al presented the results of the research on detecting low concentrations of DFC in standard solutions and grape extract using the SERS technique, with the SERS substrate made of silver coated gold nanoparticles aggregates.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In 2016 Huang and coauthors reported the use of colloidal gold nanoparticles purchased from OptoTrace Technologies to detect lowconcentration DFC in pak choi extract. 13 In that study the authors achieved a DFC detection limit of 0.413 mg L À1 . In a more recent publication (2019) Wang et al presented the results of the research on detecting low concentrations of DFC in standard solutions and grape extract using the SERS technique, with the SERS substrate made of silver coated gold nanoparticles aggregates.…”
Section: Introductionmentioning
confidence: 87%
“…With the molecular formula of C 19 H 17 Cl 2 N 3 O 3 , DFC is a broad-spectrum triazole bactericide pesticide that acts by preventing the ergosterol biosynthesis and inhibiting steroid demethylation. [12][13][14] This pesticide is widely used for crop protection against various fungi diseases such as gray mold, leaf spot, powdery mildew, and black spot. 13,14 However, the abuse of DFC may cause negative effects on human health and the ecological environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant health condition related changes are chemical, physical and microbial changes that can be described by kinetic model chemical reactions. Changes in the plant health condition during infection may be related to kinetic characteristics, such as reaction rate constants and activation energies [25,26] . Most plant health indexes changes shown in the scatter diagram can be described by the exponential function or power function.…”
Section: Development Of the Model Based On Chemical Kineticsmentioning
confidence: 99%
“…ProRaman L (Enwave) SERS tag (d) 210 cfu/ml Madiyar et al [70] Ag NPs (a) 0.31 ppm Zheng et al [67] (Continues) Huang et al [138] Forbidden substances Melamine BWS465 (B&W Tek) Ag NPs impregnated in hydrophobic paper (pen writing) (b) 0.33 ppm (milk) Han et al [139] BWS465 (B&W Tek) Ag NPs impregnated on filter paper (b) 1 ppm (milk) Li et al [140] Thin-film chromatography Home-built Ag NPs aggregated on silica nanospheres (b) 63 ppb Yazdi and White [132] Microfluidics MiniRam II (B&W Tek) Au NPs (a) 0.1-0.2 ppm (milk powder, wheat bran, etc. )…”
Section: Escherichia Colimentioning
confidence: 99%